2014
DOI: 10.1093/gji/ggu286
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency Po/So guided waves in the oceanic lithosphere: II—heterogeneity and attenuation

Abstract: S U M M A R YIn the western Pacific, high-frequency seismic energy is carried to very great distances from the source. The Po and So phases with observed seismic velocities characteristic of the mantle lithosphere have complex and elongated waveforms that are well explained by a model of stochastic heterogeneity. However, in the eastern part of the Pacific Basin equivalent paths show muted Po and weak, or missing, So. Once established, it is hard to eliminate such guided Po and So energy in the mantle lithosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 33 publications
9
35
1
Order By: Relevance
“…The observation of Kennett et al [2014] of less efficient Po and So propagation in younger lithosphere (higher temperatures and attenuation) would be consistent with the introduction of heterogeneity in the general neighborhood of the ridge crest, with contrasts masked by the presence of strong attenuation but having a stronger influence on the wavefield as the lithosphere cools. Kawakatsu et al [2009] have proposed the presence of a ''mille-feuile'' structure in the oceanic asthenosphere, with elongated pods of partial melt, to explain the contrasts with the lithosphere seen in S wave Geochemistry, Geophysics, Geosystems…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…The observation of Kennett et al [2014] of less efficient Po and So propagation in younger lithosphere (higher temperatures and attenuation) would be consistent with the introduction of heterogeneity in the general neighborhood of the ridge crest, with contrasts masked by the presence of strong attenuation but having a stronger influence on the wavefield as the lithosphere cools. Kawakatsu et al [2009] have proposed the presence of a ''mille-feuile'' structure in the oceanic asthenosphere, with elongated pods of partial melt, to explain the contrasts with the lithosphere seen in S wave Geochemistry, Geophysics, Geosystems…”
Section: Introductionsupporting
confidence: 56%
“…Across the Northwest Pacific region, the apparent velocity for Po is 8.1 km/s and for So is 4.6 km/s. Similar properties as observed for regions of efficient Po and So propagation in other parts of the Pacific basin [ Kennett et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies (Kennett et al, ; Kennett & Furumura, ) that model a more comprehensive set of seismograms with 2D waveform simulations have confirmed these early results and, furthermore, have shown that the lithospheric mantle plays the dominant role in transmitting P o and S o energies. Scattering from fine‐scale heterogeneities in the lithospheric mantle with high (20:1) horizontal‐to‐vertical aspect ratios reinforces the effects of the crust and water column, subsequently producing complex high‐frequency arrivals with long codas.…”
Section: Using Po and So Waves To Infer Lithospheric Propertiesmentioning
confidence: 74%